2001
DOI: 10.1002/ijc.1418
|View full text |Cite
|
Sign up to set email alerts
|

Elevated expression of vacuolar proton pump genes and cellular ph in cisplatin resistance

Abstract: V-ATPases are proton-translocating enzymes, which are found not only in numerous intracellular organelles but also in the plasma membranes of many eukaryotic cells. Using differential display, we have identified one of the proton pump subunit genes, ATP6C, as a cisplatin-inducible gene. Northern blot analysis demonstrated that expression of other members of the subunit is inducible by cisplatin treatment. Proton pump gene expression is also upregulated in 3 independent cisplatin-resistant cell lines but not in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
110
0
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 33 publications
(38 reference statements)
2
110
0
1
Order By: Relevance
“…Endocytosis and lysosome function in CP-r cellswas also found to be significantly higher than that of the sensitive parental cells (Murakami et al, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…Endocytosis and lysosome function in CP-r cellswas also found to be significantly higher than that of the sensitive parental cells (Murakami et al, 2001).…”
Section: Discussionmentioning
confidence: 85%
“…These mediums were purchased from Nissui Seiyaku (Tokyo, Japan) and contained 10% fetal bovine serum. The cisplatin-resistant KB/CP4 and P/CDP6 cells were derived from KB and PC3 cells as described previously (Murakami et al, 2001) and found to be 23-63-fold more resistant to cisplatin than their parental cells (Fujii et al, 1994). Vincristine-resistant KB/VJ300 cell derived from KB was generated as described previously (Kusaba et al, 1999).…”
Section: Cell Culturementioning
confidence: 99%
“…9 In brief, reverse transcription was carried out using 9 anchored primers. Twenty-four primers of 10 mer were used in a PCR with the appropriate anchored primer.…”
Section: Differential Displaymentioning
confidence: 99%
“…Prehybridization and hybridization were performed as described previously. 9 Isolation of genomic clones of MRP S11 and DNA sequencing MRP S11 cDNA was identified by mRNA differential display as a gene induced in cisplatin-treated KB cells. 9 MRP S11 genomic clones were isolated from a human placental genomic library in EMBL3 by screening with the cDNA.…”
Section: Northern Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation